Investigating the visual heritage of art in the Bateq Tribe at Kuala Tahan Pahang / Mohamad Norhelymy Mohd Jailani - Mohd Jailani, Mohamad Norhelymy (2014)
The ‘Orang Asli’ or original people refer to the aborigines living in Peninsular Malaysia. The major group of aborigines in peninsular Malaysia is classified into three groups, namely are The Negrito, The Senoi and The Proto Malay. This paper will focus on the Negrito group, specifically scoping on the Bateq tribe who lives in Kuala Tahan, Pahang. Most of the Bateq aborigine’s people are still living in the rural and forested areas of Malaysia. This research aims to investigate the Art and Cultural Heritages of the Bateq tribe and also to observe, understand, document and preserve their art that is now slowly dying pressured by the effect of modernization. In order to fully understand the community, an ethnographic research approach using photographic and video graphic method was adopted in this study through long term non-active field participant-observation approach. The investigation was undertaken to follow the migration of tribal community for the duration of a week at time every month, over a period of one year. This research finding would be beneficial to the local government, the Taman Negara Park Tourism Planners in providing appropriate future support initiatives and mostly to the Bateq Tribe itself.